2005
DOI: 10.1093/ajcn/81.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of a tea rich in catechins leads to a reduction in body fat and malondialdehyde-modified LDL in men

Abstract: Daily consumption of tea containing 690 mg catechins for 12 wk reduced body fat, which suggests that the ingestion of catechins might be useful in the prevention and improvement of lifestyle-related diseases, mainly obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
271
4
25

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(324 citation statements)
references
References 32 publications
14
271
4
25
Order By: Relevance
“…The weight loss effect due to CH-19 Sweet may have been clearly demonstrated by the precise experimental design, or capsiate may have been more effective than capsaicin. Nagao et al have reported that the ingestion of tea rich in catechins for four weeks reduced body fat by 0.5 kg, 37) and St-Onge et al have reported that the ingestion of medium-chain triacylglycerols for four weeks reduced body fat by 0.8 kg. 38) Since the ingestion of CH-19 Sweet for two weeks reduced body fat by 0.6 kg, CH-19 Sweet is suggested to be as effective for reducing body fat as such compounds as catechins and medium-chain triacylglycerols.…”
Section: Discussionmentioning
confidence: 99%
“…The weight loss effect due to CH-19 Sweet may have been clearly demonstrated by the precise experimental design, or capsiate may have been more effective than capsaicin. Nagao et al have reported that the ingestion of tea rich in catechins for four weeks reduced body fat by 0.5 kg, 37) and St-Onge et al have reported that the ingestion of medium-chain triacylglycerols for four weeks reduced body fat by 0.8 kg. 38) Since the ingestion of CH-19 Sweet for two weeks reduced body fat by 0.6 kg, CH-19 Sweet is suggested to be as effective for reducing body fat as such compounds as catechins and medium-chain triacylglycerols.…”
Section: Discussionmentioning
confidence: 99%
“…The obesity pandemic has accelerated cell, animal, and human research on the anti-obesity effects of flavonoids (Borchardt and Huber 1975;Melzig 1996;Hase et al 2001;Nagao et al 2001Nagao et al , 2005Nagao et al , 2007Singh et al 2003;Alexander 2006;Greenberg et al 2006;Harwood et al 2007;Bose et al 2008;Egert et al 2008;Ito et al 2008;Stewart et al 2008;Liu et al 2009;Faria et al 2010;Grove and Lambert 2010;Zhu et al 2010). For example, several animal studies indicate that 3-15 weeks of supplementation with green tea extract and epigallocatechin gallate (EGCG) reduce body mass and fat mass (Bose et al 2008;Ito et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The catechins in green tea may increase thermogenesis and fat oxidation by inhibiting catechol-O-methyltransferase, leading to increased expression of norepinephrine and heightened sympathetic nervous system activity (Borchardt and Huber 1975). Epidemiological research supports the anti-obesity influence of green tea intake (Grove and Lambert 2010), and controlled human trials indicate a small but significant decrease in body mass, waist circumference, and body fat in subjects randomized to green tea extract supplementation (Hase et al 2001;Nagao et al 2001Nagao et al , 2005Nagao et al , 2007. Other polyphenols such as soy isoflavones demonstrate positive effects on weight loss in humans.…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying the antiobesity effects of tea Cat in humans and rodents. 18,19 We previously demonstrated that long-term intake of tea Cat is beneficial in reducing HF diet-induced obesity, and that this effect might be attributed, at least in part, to the activation of lipid metabolism in the liver. 18 Although there have been many investigations of the beneficial effects of both Ex and some food components, little is known about their combined effects on the development of obesity.…”
Section: Introductionmentioning
confidence: 99%